2016
DOI: 10.1007/s00125-016-3887-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of register-based diabetes 10 years after a stepwise diabetes screening programme: the ADDITION-Denmark study

Abstract: Aims/hypothesis Screening programmes for type 2 diabetes inevitably find more people at high risk of developing diabetes than people with undiagnosed prevalent diabetes. We describe the incidence of diabetes for risk groups according to advancement in a screening process. Methods In 2001-2006, a diabetes screening programme based on the Danish diabetes risk score and measures of HbA 1c and glucose was carried out in Danish general practices. The present study includes 13,249 individuals with low diabetes risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…The presence of IGT conferred a lower risk than IFG, while the combination of both multiplied the risk of developing diabetes, especially in women. A similar effect has been found in the ADDITION-Denmark study 26 . The importance of detecting an early dysglicemia lies not only in the increased risk of developing diabetes over time, but also in the higher risk of developing cardiovascular and renal disease, and the higher mortality than normoglycemic subjects 27 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The presence of IGT conferred a lower risk than IFG, while the combination of both multiplied the risk of developing diabetes, especially in women. A similar effect has been found in the ADDITION-Denmark study 26 . The importance of detecting an early dysglicemia lies not only in the increased risk of developing diabetes over time, but also in the higher risk of developing cardiovascular and renal disease, and the higher mortality than normoglycemic subjects 27 .…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to the fact that these variables are not causative of diabetes, but they rather share a common pathophysiology, probably linked to the loss of insulin sensitivity 25 . The main predictor variable has been the presence of dysglicemia in the baseline study, as it happened in other studies 14,17,18,26 . The presence of IGT conferred a lower risk than IFG, while the combination of both multiplied the risk of developing diabetes, especially in women.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Danish GPs were encouraged to intervene in individuals with IFG/IGT and those with high CVD risk but without diagnosed diabetes. While small numbers of individuals were diagnosed with diabetes following screening in Denmark (1%), 1.6% were found with IFG/IGT and 48% with elevated cardiovascular risk (SCORE > 5 points), providing a larger at-risk group with the potential to benefit from interventions to prevent both diabetes and CVD [ 25 , 26 ]. Indeed, larger proportions of people in the screening practices redeemed cardioprotective medication compared with the control practices during the screening phase of the study (2001–2006).…”
Section: Discussionmentioning
confidence: 99%
“…Rasmussen et al (9) reported on the value of a very comprehensive and thought-provoking stepwise screening program that stratified diabetes risk. In addition to the other categories, they also used a lower cut point for IFG defined as ≥5.6 mmol/L but <6.1 mmol/L (100–110 mg/dL) and 2-h blood glucose <7.8 mmol/L (140 mg/dL).…”
Section: Risk Of Progression Of Ifg To Diabetes?mentioning
confidence: 99%